2021
DOI: 10.3390/f12080964
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization Sustainable Forest Supply Chain Considering Discount in Transportation System and Supplier Selection under Uncertainty

Abstract: In recent decades, the forest industry has been growingly expanded due to economic conditions, climate changes, environmental and energy policies, and intense demand changes. Thus, appropriate planning is required to improve this industry. To achieve economic, social and environmental goals, a supply chain network is designed based on a multi-period and multi-product Mixed-Integer Non-Linear Programming (MINLP) model in which the objective is to maximize the profit, minimize detrimental environmental effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Jonkman et al [17] investigated a bio-based supply chain by developing an optimization methodology taking into account the individual goals of multiple actors, and including both an economic and a carbon footprint objective function. Baghizadeh et al [18] introduced an aggregated approach concerning the forest industry and its multiplicity of products including biofuel. They developed a multiobjective, multiproduct, multiperiod mixed integer non-linear programming model for a sustainable forest supply chain by simultaneously addressing economic, environmental and social aspects under demand uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jonkman et al [17] investigated a bio-based supply chain by developing an optimization methodology taking into account the individual goals of multiple actors, and including both an economic and a carbon footprint objective function. Baghizadeh et al [18] introduced an aggregated approach concerning the forest industry and its multiplicity of products including biofuel. They developed a multiobjective, multiproduct, multiperiod mixed integer non-linear programming model for a sustainable forest supply chain by simultaneously addressing economic, environmental and social aspects under demand uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Managers' knowledge of the company environment and their capacity to receive information can both benefit from information exchange. Inter-organizational dynamics and shared learning should be influenced positively by a greater grasp of a common context and improved transparency (Baghizadeh et al, 2021;Jum'a et al, 2022).…”
Section: Supply Chain Collaboration and Environmental Performancementioning
confidence: 99%
“…Sabet et al [31] developed a consistent framework to objectively evaluate and compare the travel performance of eleven global cities. Baghizadeh et al [32] suggested a multiperiod and multiproduct Mixed-Integer Nonlinear Programming (MINLP) model considering transportation discount systems for a sustainable supply chain. Inspired by these ideas, we propose a system-based Bayesian network model for probabilistic measuring multidimensional transport sustainability and comparing cities with a consistent framework.…”
Section: Introductionmentioning
confidence: 99%